Proteomic Analysis Reveals Growth Inhibition of Coriolus versicolor by Methanol Extracts of Cinnamomum camphora Xylem - Quan Li; Xiangyang Li; Hui Lin (International Journal of Polymer Science)
The extracts of decay-resistant tree species are important research objects for the future development of wood preservatives. To understand the antifungal mechanisms of Coriolus versicolor inhibition with methanol extracts of C. camphora xylem, the protein profiles of C. versicolor were analyzed using 2-DE followed by MALDI-TOF/MS and bioinformatic analyses. The results showed that 41 protein spots were obviously changed among the 366-385 protein spots of C. versicolor treated with methanol extracts of C. camphora xylem. Twenty-one protein spots were upregulated, and 20 protein spots were downregulated. Cellular localization was performed to identify these differential proteins, and biological process and functional analysis found that 9 of these proteins were in the cytoplasm, 6 were intracellular, and 5 were in the mitochondrion. A total of 18.8% were mapped to small-molecule metabolic processes, 12.5% to cellular amino acid metabolic processes, and 10.9% to cellular nitrogen compound metabolic processes. Twenty-five percent of the differential proteins were associated with ion bonding, 15% with oxidoreductase activity, and 15% with ATPase activity and transmembrane transport activity. Downregulated expression of aspartate aminotransferase, ATP synthase alpha chain, DEAD/DEAH-box helicase, and phosphoglycerate kinase showed that the methanol extracts of C. camphora xylem disrupted functional aspects such as nitrogen and carbon metabolism, energy metabolism, hormone signal response, and glucose metabolism, eventually leading to C. versicolor inhibition.